Does the Norwegian Police Force Need a Well-Functioning Combat Mindset? - Boe, Ole; Torgersen, Glenn-Egil; Skoglund, Tom Hilding (Frontiers in Psychology, 2020)
This article discusses the apparent lack of a well-functioning combat mindset evident in the Norwegian Police Force during the terrorist attacks in Norway on July 22, 2011. We describe what a well-functioning combat mindset is and then continue to discuss challenges linked to the current mindset in the Norwegian Police Force. We then elaborate upon how the experience of an acute stress reaction may affect one’s ability to solve a mission. Then we describe how to cope with stress and the importance of a well-functioning combat mindset, and we then discuss techniques in order to build a well-functioning combat mindset. Furthermore, we describe how coping with an extreme cognitive load and a well-functioning combat mindset are related. Finally, we suggest a method for practicing combat mindset (CM-training). The combat mindset training needs to include both realistic training and systematic reflection in order to a better ability to deal with sudden and unforeseen events.